Validity and Reliability Test of European Organization for Research and Treatment of Cancer Quality of Life QuestionnaireBreast 23 in Breast Cancer Patient on Treatment - Adli, Mizanul; Shatri, Hamzah; Sutandyo, Noorwati; Suwarto, Suhendro (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Improved survival of breast cancer patients are not necessarily followed by improvement of quality of life. According to the European Organization for Research and Treatment of Cancer (EORTC), cancer patients’ quality of life are very important to be evaluated. In Indonesia, breast cancer patients cannot be assessed their quality of life accurately because there is no valid and reliable questionnaire. This study aims to prove that the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Breast 23 (EORTC QLQ-BR23) is a valid and reliable measuring instrument to be used in Indonesia. Methods. This study was a cross-sectional study. The EORTC QLQ-BR23 questionnaire was first translated into Indonesian language before being tested on 10 respondents. The translation results were then used in 100 breast cancer patients. Test-retest was assessed with intraclass correlation coefficient (ICC), while the internal consistency was assessed by Cronbach’s alpha. Construct validity was assessed by multi-trait scaling analysis and the criteria validity assessed by identifying the correlation between domains of European Organization for Research and Treatment of Cancer Quality of Life QuestionnaireCancer 30 (EORTC QLQC30) and EORTC QLQ-BR23 with Short Form 36 (SF36). Results. From September to October 2015, a total of 100 breast cancer patients on treatment were enrolled in this study. ICC value (1 hour interval) of all EORTC QLQ-BR23 domains were very good (ICC> 0.8). ICC values (30 day interval) decrease in all EORTC QLQ-BR23 domains. Almost all of the EORTC QLQ-BR23 domains have a cronbach’s alpha value > 0.7 except for the arm symptom domain (Cronbach’s alpha: 0.643). Multi-trait scaling analysis showed a fairly high correlation between the score of the questions with a score of his own domain, while the relationship of the questions to different domains always have a lower correlation than the domain itself. In criteria validity test, obtained 19 correlation with r > 0.3 between domains of EORTC QLQ-C30 and EORTC QLQ-BR23 with SF36. Conclusion. EORTC QLQ-BR23 is a valid and reliable instrument for assessing quality of life of breast cancer patients in Indonesia